Development of an Appsheet-based Inventory Application forStock Management Efficiency at PT Unilever Indonesia - Joy Tessyaloni Rosliana; Rika Nur Jaga (Records Management System Journal, 2025)
PT Unilever Indonesia Tbk is a multinational company with a large distribution and storage chain for its products, making inventory data management extremely crucial. Currently, some departments within the company still use manual recording methods, which can lead to risks such as delays, input errors, and data inconsistencies. To improve efficiency and effectiveness in inventory management, a computerized inventory management information system was designed using the Google AppSheet platform. This application was developed to facilitate the recording, tracking, and management of incoming and outgoing goods data digitally and in real-time. The method used in system development was the descriptive method. The application implementation covers the main page to the goods data input form. System testing was conducted using the blackbox testing method and showed that the application functions as intended. Maintenance was performed to ensure the system continues to operate optimally. The results of this development demonstrate that the AppSheet-based inventory application can improve efficiency and accuracy in inventory management at PT Unilever Indonesia Tbk.